Synthesis and characterisation of the ternary intermetalloid clusters {M@[As8(ZnMes)4]}3− (M = Nb, Ta) from binary [M@As8]3− precursors - Zhang, W-Q; Morgan, HWT; McGrady, JE; Sun, Z-M (Royal Society of Chemistry, 2022)
The development of rational synthetic routes to inorganic arsenide compounds is an important goal because these materials are finding applications in many areas of materials science. In this paper, we show that the binary crown clusters [M@As8]3− (M = Nb, Ta) can be used as synthetic precursors which, when combined with ZnMes2, generate ternary intermetalloid clusters with 12-vertex cages, {M@[As8(ZnMes)4]}3− (M = Nb, Ta). Structural studies are complemented by mass spectrometry and an analysis of the electronic structure using DFT. The synthesis of these clusters presents new opportunities for the construction of As-based nanomaterials.